0121 Sleep facilitates memory, but not navigation across the pubertal transition in the novel Minecraft Memory and Navigation Task. (25th May 2022) - Simon, Katharine; Fenger, Alexis; Warren, Laura; Choukas, Nathaniel; Choi, Dean; Zhang, Jing; Clemenson, Gregory; Mednick, Sara
Abstract: Introduction: The hippocampus uniquely supports the acquisition and retention of spatial information, and sleep supports the consolidation of hippocampal-dependent memories. However, support for the role of sleep in spatial memory and navigation is mixed. We developed and tested a novel Minecraft Memory and Navigation (MMN) task in adults which showed that sleep uniquely supports the memory for spatial locations, but navigation improved regardless of delay condition (Simon et al., submitted). Here, we tested participants during the developmental transition from childhood to adolescence, a time known for structural and functional hippocampal maturation. Methods: Thirty-one youth (Mage = 10.6, SD = 1.56, 9-13 years, grouped: child, early adolescent, adolescent) were administered the MNN task. Training included two free-explorations trials to learn 12 unique object-locations associations in an open-field Minecraft environment. At test, participants were cued to place objects from randomly teleported locations. They were tested twice, immediately and 12-hours later, after a period of sleep or wake. Conditions and environments were counterbalanced in a within-subject design. Each step-by-step movement was recorded for navigation analyses including path length, orientation angle, and search behaviors. Results: We found a significant benefit of sleep, compared to wake, on the spatial location accuracy when accounting for age group (F(1, 27) = 6.153, p = .02), such that similar to young adults, youth's metric accuracy of spatial locations improved. We found no change in navigation performances from Test 1 to Test 2 in either condition. Between the start and target locations, youth initiated and maintained similar trajectory angles with similar total path lengths (p's > .068). Spatial location memory did not correlate with any navigation metrics (p's > .361). Navigation metrics correlated among themselves, which withstood correction (p's < .005). Conclusion: Youth demonstrated similar sleep-dependent benefits for the metric accuracy of the spatial locations. In contrast to adults, youth's navigation performance did not improve over delay, regardless condition. Our findings are in line with sleep's promotion of hippocampal-dependent information, with retention of the spatial locations. Our data are consistent with the hypothesis that sleep does not facilitate navigation, and points to potential developmental maturation required to support navigation behaviors. Support (If Any):